2010
DOI: 10.1074/jbc.m109.075929
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of SIVmac239 Basal Long Terminal Repeat Activity and Viral Replication in Macrophages

Abstract: CCAAT/enhancer-binding protein (C/EBP) ␤ and C/EBP sites in the HIV-1 long terminal repeat (LTR) are crucial for HIV-1 replication in monocyte/macrophages and for the ability of interferon ␤ (IFN␤) to inhibit ongoing active HIV replication in these cells. This IFN␤-mediated down-regulation involves induction of the truncated, dominant-negative isoform of C/EBP␤ referred to as liver-enriched transcriptional inhibitory protein (LIP). Although binding of the C/EBP␤ isoform to C/EBP sites in the simian immunodefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 76 publications
4
37
0
Order By: Relevance
“…Several studies have demonstrated that the CCAAT/enhancer binding protein sites in the human immunodeficiency virus type 1 (HIV-1) LTR are crucial for HIV-1 replication in monocyte/macrophages and for the ability of IFN-b to inhibit ongoing active HIV replication in these cells (Henderson & Calame, 1997;Henderson et al, 1995Henderson et al, , 1996Ravimohan et al, 2010). Moreover, mutations in CCAAT/ enhancer elements have been found in the LTR region of RSV.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the CCAAT/enhancer binding protein sites in the human immunodeficiency virus type 1 (HIV-1) LTR are crucial for HIV-1 replication in monocyte/macrophages and for the ability of IFN-b to inhibit ongoing active HIV replication in these cells (Henderson & Calame, 1997;Henderson et al, 1995Henderson et al, , 1996Ravimohan et al, 2010). Moreover, mutations in CCAAT/ enhancer elements have been found in the LTR region of RSV.…”
Section: Discussionmentioning
confidence: 99%
“…In macrophage cell lines, IFNβ can induce the production of a dominant-negative form of CCAAT/enhancer-binding protein-β (C/EBPβ) that has been referred to as LIP 75,76 . LIP blocks the acetylation of histones bound to SIV DNA and reduces viral replication 75,77 . Interestingly, an inverse correlation between SIV viral loads and the ratio of C/EBPβ to LIP was observed in macaque brains 76 , suggesting a role for IFNβ-induced genes in CNS antiviral responses following SIV infection.…”
Section: Persistent and Latent Viral Infectionsmentioning
confidence: 99%
“…The DS1 C/EBP site in the SIV-LTR is particularly important for regulation by IFNβ [18]. The C-to-A substitution we identified in LTRs sequenced in vivo is within the DS1 C/EBP site.…”
Section: Resultsmentioning
confidence: 79%
“…We have previously shown using competition EMSAs that the affinity of LIP for the wild-type DS1 C/EBP site is 3.5-fold higher than that of LAP, which may contribute to the negative regulatory function of the wild-type DS1 C/EBP site with regard to SIV-LTR activity [18]. We therefore carried out competition EMSAs to determine whether the C-to-A substitution within the DS1 site alters the affinity of LAP (Figure 5) and/or LIP (Figure 6).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation